Reflection for learning, learning for reflection: Developing indigenous competencies in higher education - Bennett, Dawn; Power, A.; Thomson, Chris; Mason, Bonita; Bartleet, B. (University of Wollongong, 2016)
Reflection is an essential part of students’ critically reflective development within experientiallearning contexts; it is arguably even more important when working cross-culturally. This paper reports from a national, arts-based service-learning project in which students in creative arts, media and journalism, and pre-service teachers worked with Aboriginal people in urban and rural areas of Australia. The paper uses Ryan and Ryan’s (2010) 4Rs model of reflective thinking for reflective learning and assessment in higher education to ascertain the effectiveness of the project work toward engendering a reflective mindset. The paper discusses how students learned to engage in critical self-monitoring as they attended to their learning experiences, and it describes how they “wrote” their experiences and shaped their professional identities as they developed and refined the philosophy that related to their developing careers. Examples taken from the narratives of students, community partners and academic team members illustrate the principal finding, which is that through a process of guided reflection, students learned to reflect in three stages: a preliminary drawing out of existing attitudes and expectations; a midway focus on learning from and relating to past experiences; and a final focus on reciprocal learning, change and future practice. The three stages were apparent regardless of program duration. Thus, program phase rather than academic year level emerged as the most important consideration when designing the supports that promote and scaffold reflection.